2015
DOI: 10.1155/2015/482863
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bacteriophage Preparations on Intracellular Killing of Bacteria by Phagocytes

Abstract: Intracellular killing of bacteria is one of the fundamental mechanisms against invading pathogens. Impaired intracellular killing of bacteria by phagocytes may be the reason of chronic infections and may be caused by antibiotics or substances that can be produced by some bacteria. Therefore, it was of great practical importance to examine whether phage preparations may influence the process of phagocyte intracellular killing of bacteria. It may be important especially in the case of patients qualified for expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 58 publications
(61 reference statements)
2
27
0
1
Order By: Relevance
“…The effect of phage therapy on IKB has been studied by Jończyk-Matysiak et al [31]. As could be expected, IKB of patients prior to therapy was generally reduced while the therapy did not cause further reduction in IKB of a standard Escherichia coli B strain.…”
Section: • Phages and Phagocytesmentioning
confidence: 87%
“…The effect of phage therapy on IKB has been studied by Jończyk-Matysiak et al [31]. As could be expected, IKB of patients prior to therapy was generally reduced while the therapy did not cause further reduction in IKB of a standard Escherichia coli B strain.…”
Section: • Phages and Phagocytesmentioning
confidence: 87%
“…There are also suggestions that some species of phage may promote the opsonization of bacteria by adhering to the bacterial surface and acting as a target for antibody binding (157). In addition, there are reports that phages may be induced when their bacterial host is phagocytosed, lysing the bacteria and promoting clearance (149,158). Together, these data suggest that lytic phages may promote opposite effects on bacterial clearance compared to Pf.…”
Section: The Emerging Picture Of Phage/immune Interactionsmentioning
confidence: 99%
“…Our data on monitoring phagocytosis by neutrophils and monocytes of patients on phage therapy suggest that the therapy may instead correct existing deficiencies in phagocyte functions (see above). In fact, we have shown that phages – both in vitro and in vivo – do not adversely affect the ability of phagocytes to kill bacteria – both standard strains as well as specific pathogens isolated from patients ( Jończyk-Matysiak et al, 2015 ). Also, phages do not impair migratory activity of human phagocytes in vitro ( Kurzępa, 2011 ), whereas they may markedly diminish tissue infiltration with those cells at the foci of inflammation ( Górski et al, 2006a ; Miernikiewicz et al, 2016 ).…”
Section: Phages and The Immune Systemmentioning
confidence: 99%